2013
DOI: 10.3892/ijo.2013.1971
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglycerate kinase 1 as a promoter of metastasis in colon cancer

Abstract: Oxidative stress due to intratumoral hypoxia in solid cancer has been shown to be associated with increased mortality. Phosphoglycerate kinase 1 (PGK1) is an enzyme of the glycolytic pathway, which is regulated by hypoxia-inducible factor-1α (HIF-1α) and has been described for its role in tumor progression and metastasis in several malignancies. We investigated whether the expression of PGK1 varies between metastatic and non-metastatic colon cancer. We compared PGK1 expression in colon cancer patients either w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 33 publications
1
67
0
Order By: Relevance
“…The plasmid pBS 16 114b:1, harboring the HPV16 114/b wt genome, was kindly provided by M. Dürst (40), and plasmid hPGK1 pEF-IRES-P, encoding the cDNA for human phosphoglycerate kinase 1 (PGK1), was kindly provided by D. Zieker (41). The HPV16 E8Ϫ and E8 KWK mt genomes were constructed by overlap extension PCR using specific primers and verified by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…The plasmid pBS 16 114b:1, harboring the HPV16 114/b wt genome, was kindly provided by M. Dürst (40), and plasmid hPGK1 pEF-IRES-P, encoding the cDNA for human phosphoglycerate kinase 1 (PGK1), was kindly provided by D. Zieker (41). The HPV16 E8Ϫ and E8 KWK mt genomes were constructed by overlap extension PCR using specific primers and verified by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…10 PGK1 has been associated with carcinogenesis and metastasis in various malignancies. 11,12 This has prompted investigations into PGK1 as a potential oncogenic molecular biomarker and an indicator of poor prognosis in pancreatic cancer, 13 gastric cancer, 14 neuroblastoma, 15 and hepatocellular carcinoma. 16 A recent study revealed that PGK1 was a prognostic biomarker of chemoresistance to paclitaxel treatment in patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In our surgical samples we have identified three distinct isoforms of PGK1 all increased with respect to the normal tissues. Many types of cancers, including those of the breast [47], the colon [48], the liver [49] and others, have been shown to exhibit an increased expression of PGK1. Indeed, it has been demonstrated that, in addition to its role as a glycolytic enzyme, PGK1 may act as a promoter of cancer progression and induce chemoresistance for some type of drugs [47,48].…”
Section: Phosphoglycerate Kinase 1 Pgk1 (Pgk1)mentioning
confidence: 99%